The Relative Growth Rates of the Two-dimensional and Three-dimensional Waves in the Atmosphere - Camerlengo, Alejandro Livio; Saadon, Mohd Nasir (Universiti Putra Malaysia Press, 1999)
Using a simple analysis the growth rate of two-dimensional and three-dimensional waves in the atmosphere is addressed. It is verified that a two-dimensional wave grows faster than a three-dimensional wave.